DIVERSITY OF ARBUSCULAR MYCORRHIZAL FUNGI ASSOCIATED WITH THE RHIZOSPHERE OF PHOENIX DACTYLIFERA L. IN SEMI-ARID SOILS. - AMEETA SHARMA; NEHA GHEEK BATRA (International Journal of Pharma and Bio Sciences, 2014)
In order to survey biodiversity and root colonization of arbuscular mycorrhizal fungi (AMF) on date palm (Phoenix dactylifera L.) tree, the present study was undertaken in semi-arid areas of Jaipur district at fifteen sites. The genera identified were Gigaspora, Glomus, Scutellospora, Entrophosphora and Sclerocystis. The root colonization by AM fungi varied significantly, ranging from 78% to 93% in date palms rhizosphere. Gigaspora species were found in abundance and their occurrence frequency ranged from 60-70%, Glomus species from 40-50%, Sclerocystis upto 30%, Scutellospora from 10-20% and Entrophosphora upto 10%. Overall evaluation revealed that the root colonization and the spore population varied to different extend. The AM colonization and number of spores in date palm roots were found to be negatively correlated with soil phosphorus content and electric conductivity of soil samples and positive correlation between number of spores and root colonization